2015
DOI: 10.4236/ojpm.2015.56031
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perceived Health Status and Health Practices in the General Adult Population in Japan

Abstract: The objective of this study was to explore the relationship of perceived health status and Breslow's seven health Practices(7-8 hours of sleep per night, maintaining a healthy weight, moderate or no alcohol intake, regular physical activity, no eating between meals, eating breakfast, and having never smoked cigarettes) in adult residents in Kumamoto Prefecture Japan. We used 2011 data from the "Health Japan 21" program in Kumamoto Prefecture, a study consisting of 2519 adults aged from 20-74 years. Data for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…Of the health-related factors, perceived health status and alcohol consumption were found to be strongly related to current smoking. Lifestyle factors such as smoking status, drinking habits, food consumption, and physical activity are generally linked to perceived health status [25], and poor perceived health has previously been associated with current smoking [26]. Alcohol consumption was shown to be a major barrier to smoking cessation among young adults [9,10,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Of the health-related factors, perceived health status and alcohol consumption were found to be strongly related to current smoking. Lifestyle factors such as smoking status, drinking habits, food consumption, and physical activity are generally linked to perceived health status [25], and poor perceived health has previously been associated with current smoking [26]. Alcohol consumption was shown to be a major barrier to smoking cessation among young adults [9,10,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study, satisfaction with health was predicted by symptoms and present medication [ 19 ]. A recent study found an association with life satisfaction [ 20 ]. Both studies observed a steady association between satisfaction and health and health-related behaviors, called good practices, such as having exercise, no snacks, and maintaining a good BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety regarding health (general, physical, mental, and any others) was addressed to screen for symptoms of mental problems, which can be common among those of working age, such as depression [ 16 , 17 ]. Based on previous studies [ 18 20 ], satisfaction in terms of health (well-satisfied and satisfied vs. not very satisfied and unsatisfied) was explored because level of health satisfaction was expected to predict comprehensive health associated with lifestyle and sociodemographic characteristics [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Health related lifestyle was measured using questions adapted from Breslow׳s lifestyle index ( Belloc, Breslow & Hochstim, 1971 ) which has been validated and widely used in previous studies ( Haruyama et al, 2012 , Noguchi et al, 2015 , Breslow and Enstrom, 1980 ). These questions and possible responses were scored as follow: (1) how many hours sleep did you usually get a night?…”
Section: Methodsmentioning
confidence: 99%